Sense-making strategies and help-seeking behaviours associated with urgent care services: a mixed-methods study - Turnbull, J; McKenna, G; Prichard, J; Rogers, A; Crouch, R; Lennon, A; Pope, C (NIHR Journals Library, 2019)
Background Policy has been focused on reducing unnecessary emergency department attendances by providing more responsive urgent care services and guiding patients to ‘the right place’. The variety of services has created a complex urgent care landscape for people to access and navigate.